2018
DOI: 10.3201/eid2410.180253
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Pneumococcal Disease in Refugee Children, Germany

Abstract: Refugee children in Germany are not routinely given a pneumococcal conjugate vaccine. Cases of invasive pneumococcal disease (IPD) in 21 refugee children were compared with those in 405 Germany-born children for 3 pneumococcal seasons. Refugee children had significantly higher odds of vaccine-type IPD and multidrug-resistant IPD than did Germany-born children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…A number of studies examined seroprevalence as a correlate of vaccine protection, and varying antibody levels were detected for those who responded as having received specific vaccinations [ 44 , 45 , 52 , 57 , 60 , 61 , 63 , 78 , 83 , 88 , 90 , 91 , 97 , 99 ]. For example, one study observed that, among 200 migrant children, for protection against HBV, only 118 (59%) had anti-HBs ≥1000 UI/L compared to 23 (11%) having no detectable antibodies (<10 IU/L) [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies examined seroprevalence as a correlate of vaccine protection, and varying antibody levels were detected for those who responded as having received specific vaccinations [ 44 , 45 , 52 , 57 , 60 , 61 , 63 , 78 , 83 , 88 , 90 , 91 , 97 , 99 ]. For example, one study observed that, among 200 migrant children, for protection against HBV, only 118 (59%) had anti-HBs ≥1000 UI/L compared to 23 (11%) having no detectable antibodies (<10 IU/L) [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…Asylum-seeking children have more mental health problems than the local population (Ehntholt et al, 2018;Hanes et al, 2019;Jensen et al, 2019;Kien et al, 2019;Norredam et al, 2018;Yalın Sapmaz et al, 2017), and they are likely to experience post-traumatic stress disorder (Ehntholt et al, 2018;Jensen et al, 2019;Kien et al, 2019). Other health issues observed among asylum-seeking children include communicable diseases (Hanes et al, 2019;Hirani et al, 2018;Mueller-Hermelink et al, 2018;Perniciaro et al, 2018), noncommunicable diseases (Hanes et al, 2019;Hirani et al, 2018), nutrition and growth concerns (Grammatikopoulou et al, 2019;Hanes et al, 2019;Hirani et al, 2018), physical symptoms (Hanes et al, 2019;Hirani et al, 2018), sexual health issues (Hirani et al, 2018;Wikholm et al, 2020), and dental problems (Hanes et al, 2019). The literature supports a clear need for health care.…”
Section: Introductionmentioning
confidence: 99%